Microneedle fractional radiofrequency treatment of facial photoageing as assessed in a split‐face model. (1st February 2019) - Liu, T.‐M.; Sun, Y.‐M.; Tang, Z.‐Y.; Li, Y.‐H.
Summary: Background: A new therapeutic device passes radiofrequency energy through microneedles to targeted tissue. Three‐dimensional photography may be useful for evaluating the clinical efficacy of microneedle fractional radiofrequency (MFR) used on the appearance of rhytids and to improve facial laxity. Aim: To evaluate the efficacy and safety of MFR in the treatment of facial photoageing. Methods: In total, participants with facial photoageing were enrolled in the study. All volunteers were randomized to receive split‐face treatments with MFR 2 months apart. The participants self‐evaluated at baseline, Days 1–7, and Months 1 and 3 after the final treatment. Objective evaluation was provided by a three‐dimensional in vivo imaging system. In addition, skin melanin index, erythema index, immediate reactions, healing times and other adverse effects were evaluated. Results: Compared with the untreated side, the treated side of most participants improved, based on clinical assessments at the 1‐ and 3‐month follow‐up visits after treatment. Both objective and participative assessments were satisfactory. The participants demonstrated a decrease of roughness parameter (Sa) value at each follow‐up visit. Compared with pretreatment value, Sa decreased significantly at Months 1 and 3 on the treated side ( P < 0.05). Minimal and reversible adverse effects and rapid healing were recorded. Conclusions: MFR appears to be an excellent treatment for photodamaged facial skin in Chinese patients.